2021
DOI: 10.1002/star.202100193
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Freeze‐Thaw Stability of Rice Starch by Soybean Protein Hydrolysates‐Xanthan Gum Blends and its Mechanism

Abstract: To improve the freeze-thaw stability of rice starch (RS), the soybean protein hydrolysates (SPHs), xanthan gum (XG), and the blends of SPHs with XG (SPHs-XG) are added. The syneresis, thermal, texture, rheological properties, and morphological features of samples during seven freeze-thaw cycles (FTCs) are investigated by syneresis measurement, differential scanning calorimetry (DSC), textural properties analysis (TPA), dynamic rheological, NMR, and SEM. As a result, SPHs-XG is more effective for improving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[ 30 ] Studies by Luo et al. [ 65 ] suggested that the addition of other complex of protein/carbohydrates from soybean protein hydrolysates‐xanthan gum blends might be the strategy to enhance RSC in food and food products.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30 ] Studies by Luo et al. [ 65 ] suggested that the addition of other complex of protein/carbohydrates from soybean protein hydrolysates‐xanthan gum blends might be the strategy to enhance RSC in food and food products.…”
Section: Resultsmentioning
confidence: 99%